SEMANTIC ISSUES OF TRANSLATING AMERICAN SOCIOCULTURAL STEREOTYPES - Svitlana Lyubymova; Nadezhda Tomasevich; Olena Mardarenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
Devoted to problems of translations, the work presents a qualitative analysis of semantic peculiarities of sociocultural stereotypes that influence the solutions of a translator in the process of interpreting. We hypothesised that a specific social category that exists in a source culture in the form of pragmatic predispositions, namely a sociocultural stereotype, which has no equivalent notion as well as a word in translation culture and language, is a lacunar stereotype. The words denoting sociocultural stereotypes evoke numerous images, built in accordance with cultural and ethnic patterns, therefore such stereotypes are almost impossible to preserve in translation language. The work is aimed to recognise parameters of lacunarity, to determine the semantic components that frame the reference in translation, and to suggest the ways in rendering lacunar sociocultural stereotypes. The data for research material is taken from the Corpus of Contemporary American English. As it was ascertained in the course of semantic analysis of lexical units that denote sociocultural stereotypes, the lacunarity of these stereotypes for a target culture is determined by linguistic, historic, social, and cultural parameters. A lack of appropriate lexical means in the translation language inevitably leads to some losses in denotative meaning, whereas connotative meaning is not possible to render adequately because of discrepancy between axiological systems of source and receiving cultures. Decomposition of stereotype pragmatic information into figurative, historic and connotative components enables to emphasise relevant for a particular context pragmatic component. Highlighting the relevant component, with consideration for peculiarities of represented genre and context, is a solution to convey a part of the original pragmatic information. We deduced two major techniques for translation of sociocultural stereotypes: (1) interpreting the unknown for the recipient word or (2) introducing a cultural element, which is familiar to the recipient. Representation of socio-cultural stereotypes by means of another language requires rigorous analysis of pragmatic information that stereotypes code. The work outlines future prospects for research of lacunarity and strategies to eliminate lacunae in a target culture.